A neoclassical realist explanation of Indonesia's involvement in Muslim-related secessions in non-Muslim countries. Issue 3 (September 2019) - Sari, Angguntari C
This article attempts to test the ethnic ties theory and provides an alternative explanation for why Indonesia as the largest Muslim country in the world has been inconsistent in its support for Muslim separatists. In this article, I use a Mill's method of most similar system design and examine variation in Indonesia's foreign policy towards Muslim secessionism taking place in non-Muslim countries over time. Since Indonesia's independence in 1945, it has frequently supported the non-Muslim host states, has supported the Muslim separatists on some occasions, and has either adopted an ambivalent foreign policy/supported both the host states and separatist groups or adopted a neutral stance/neither supported the host states nor the separatist groups on other occasions. I suggest a neoclassical realist explanation and argue that specific foreign policy outcomes in the context of Muslim separatists versus non-Muslim host states are shaped by the perception of leading policy makers on the extent to which support for the conflicting parties in the secessionist conflicts can hinder or facilitate the achievement of vital national interests and ultimately the state's international as well as the level of domestic political constraints specifically the public demand to assist the separatist movements.